The Problems of Formation of the National System of Personnel Training for Vocational Schools: Historical and Genetic Analysis - E. M. Dorozhkin; I. A. Сhernoskutova (Russian State Vocational Pedagogical University, 2020)
Introduction. In Russia, the main prerequisite for scientific and industrial modernisation has always been the achievement of critical points of development gap with advanced Western countries, when the implementation of reforms has become a decisive condition for ensuring national security and survival of the state itself. The most important issue in each historical modernisation cycle was the training of scientific and industrial personnel, carried out in accordance with the next strategic tasks.The aims of the present research are the following: to evaluate the effectiveness of the mechanisms to increase human resources in the system of training skilled workers used in the Soviet and post-Soviet periods; to determine the role and importance of higher vocational and pedagogical education, and on this basis, to predict possible ways of its further development.Methodology and research methods. The main methodological tool used in the work is the historical and genetic approach, which allowed the authors to identify and interpret the logic of the centennial process of gradual formation of the Soviet model of vocational education and training (VET); to analyse the requests for education of teachers and masters of industrial training, changing both in terms of scale and requirements, in particular, the requirements to the level of qualification and general culture, and to determine the range of the most effective forms towards meeting these requirements.Results and scientific novelty. The peculiarities of phased development of the Russian system of qualified workers' training were studied through a comprehensive analytical review of historical literature, documentary sources and statistical data. In this context, the principles of recruiting the teaching staff and masters of industrial training are discussed. Based on historical facts, it is concluded that the restructuring of vocational and pedagogical education is chronically lagged in relation to the urgent needs of the stationary system of young workers' training.The paper reveals the reasons for the lack of the adequate tasks of holistic concept and the general training programme for teachers and masters in the field of VET throughout almost the entire Soviet period. The authors show a direct connection with this crisis in the system of State labour reserves, which, by the end of the 1950s, was not able to adapt to changes in the technological level of Soviet industry and agriculture, despite the attempts to create specialised types of educational institutions. The serious problems with providing vocational schools with teaching personnel in the 1960s and 1970s are clarified. Along with continuing attempts to "patch up personnel holes" through the administrative direction of qualified workers and competent managers to work in vocational schools, it was initiated to create a network of industrial-pedagogical technical schools. The next logical step was the opening of Sverdlovsk Engineering and Pedagogical Institute in 1978, which started the formation of the system of specialised higher vocational and pedagogical education. Today, it is the Russian State Vocational Pedagogical University, in which the ideas of integration of sectoral and psycho-pedagogical training continue to be developed. The university professionally prepares and trains competent and multi-skilled specialists in the modern conditions of qualification.Practical significance. The materials of the present article can be useful for historians of education, teachers, theorists and practitioners engaged in the development of vocational education system.